Política educacional e espaço físico escolar: a infraestrutura como dimensão na garantia de padrão de qualidade - Dallagnol, Raquel (2015)
This work is in the field of educational policies and aims to analyze the regulatory frameworks and national political actions proposed in the period after 1988 with regard to school physical space. It is verified if this aspect is presented as a factor for the establishment of quality conditions in Brazilian basic education. The research is structured in a descriptive qualitative approach that uses bibliographic and documentary sources. Firstly, the concepts and analytical models of public policy are focused, highlighting the cognitive approach to policies. For this approach, public policies are established in a scenario of dispute among several actors. These actors present ideas that result from social interactions and, once established, they end up forming cognitive frameworks that underlie the cognitive matrices (public policies). Through this perspective of public policy analysis, we investigated the educational policies towards school physical space in the temporal context after 1988. However, the survey also covers school physical space since the republican period. In the context of the First Republic, school groups and the concern with the construction of buildings intended for education are highlighted. From the 1930s, the proposals articulated by Teixeira, especially in projects carried out in Bahia and Rio de Janeiro, are evidenced. In the 1960s and 1970s, the agreements between the Ministry of Education (MEC) and the United States Agency for International Development (USAID), which led to the implementation of multi-purpose schools, are emphasized. In the same period, there was the creation of agencies responsible for school construction, such as Centro Brasileiro de Construções e Equipamentos Escolares (CEBRACE) and Centro de Desenvolvimento e Apoio Técnico da Educação (CEDATE). In the 1980s, there was the creation of Centros Integrados de Educação Pública (CIEP) and Centros Integrados de Atendimento à Criança (CIACs). The school physical structure of CIEPs and CIACs came to meet the political prospects of that scenario, which aimed to democratization with education quality, ensuring access and permanence of students in basic public school. From 1988 onwards, we analyzed school physical space in documents such as the Constitution of 1988, Lei de Diretrizes e Bases da Educação (LDB, Law n.º 9.394/96), Plano Decenal de Educação para Todos (1993-2003), Plano Nacional de Educação (PNE) and the School Census; in programs and plans as Fundo de Desenvolvimento da Escola (Fundescola), Plano de Ações Articuladas (PAR) and Programa Nacional de Reestruturação e Aquisição de Equipamentos para a Rede Escolar Pública de Educação Infantil (Proinfância); and in the documents of Conferência Nacional de Educação (CONAE). Through the analysis of these writings, we found aspects related to school physical space and how it is articulated as a dimension to guarantee the improvement of education quality. In this process, we present the concept of quality linked to intra and extra-school factors, which appear as a quality analysis parameter set by the normative frameworks.